Coronary subclavian steal syndrome—is there a need for routine assessment for subclavian artery stenosis following coronary bypass surgery?. Issue 12 (21st November 2018) - Waduud, M A; Giannoudi, M; Drozd, M; Malkin, C J; Patel, J V; Scott, D J A
Abstract: Subclavian artery stenosis (SAS) resulting in coronary subclavian steal syndrome (CSSS) is a common but under recognized pathology following coronary artery bypass surgery (CABG). Patients with SAS may be asymptomatic due to the sub-clinical diversion of blood flow from the myocardium and retrograde blood flow during catheter angiography in the left internal mammary artery (LIMA) may be the first suggestion of CSSS. The management of SAS, causing CSSS, may rarely require acute assessment and intervention. However, full anatomical assessment of the stenosis morphology may be limited on fluoroscopy. Correction of SAS may be essential to achieve effective reperfusion therapy.